ENVIRONMENT-ASSISTED QUANTUM TRANSPORT IN OPEN SYSTEMS - Dwiputra, Donny
The properties of a quantum system can be altered in myriad ways by applying an external periodic driving force or by connecting it to a environmental reservoir as an open quantum system. One of the phenomena which may be applied to the development of the future quantum technology is the quantum transport in systems with dissipative effects and phase randomization (dephasing) due to its environment. Interestingly, in certain conditions, instead of hindering the transport, the environmental noise may enhance the transport efficiency; the counterpart in nature is, for instance, in the photosynthetic complexes. This dissertation studies the model which explains how an external periodic force can also enhance the open system transport efficiency, and also will be investigated is the characteristics of environment-assisted transport in systems with localization-delocalization transition that possesses a mobility edge. The quantum transport behavior is studied in a network of two-states system (qubit) in presence of on-site and off-diagonal periodic external force. This work is a generalization of the dephasing-assisted quantum transport where noise is beneficial to the transport efficiency. Using Floquet-Magnus expansion extended to Markovian open systems, we analytically derive transport efficiency and compare it to exact numerical results. We find that periodic driving may increase the efficiency at frequencies near the coupling rate. On the other hand, at some other frequencies the transport may be suppressed. We then propose the enhancement mechanism as the ramification of interplay between driving frequency, dissipation, and particle trapping. The environment-assisted quantum transport (ENAQT) will be generalized to models containing localization-delocalization transition with a mobility edge. In this study, we investigate how the presence of a one-dimensional single-particle mobility edge can generate strong ENAQT. For this purpose, we study the energy current of a generalized Aubry-Andre-Harper tight binding model coupled at its edges to spin baths of differing temperature and dephasing noise along the system. We find that the ENAQT increases by some orders of magnitude and depends on the number of localized eigenstates and disorder strength nonmonotonically. We show that this enhancement is the result of the cooperative interplay between population spread and localization.